Factors Affecting the Catalytic Performance of Nano‐catalysts. Issue 4 (24th December 2021) - Yang, Hongling; Wu, Yue; Zhuang, Zewen; Li, Yang; Chen, Chen
Comprehensive Summary: Nano‐catalysis plays a vital role in the industrially chemical transformations. The increasingly severe energy crisis and environmental issues spur scientists to exploit novel nano‐catalysts in diverse fields. It is essential to understand the fundamental physicochemical properties of nano‐catalysts to develop efficient systems, whose design can be subsequently precisely tuned at the atomic level. In this review, we summarize several key factors affecting the catalytic activity of nano‐catalysts, including structure, composition, size, and interface, providing guidance for the atomic level control of high‐efficient nano‐catalysts. Finally, we present a brief conclusion and some thoughts on nano‐catalysis. What is the most favorite and original chemistry developed in your research group? Nanomaterials for catalysis and renewable energy. How do you supervise your students? I always encourage my students to innovate, persist and enjoy their researches. What is the most important personality for scientific research? Strong interest. What are your hobbies? What's your favorite book(s)? Reading, travelling and gaming. My favorite books are novels that give me a variety of different experiences. How do you keep balance between research and family? I always try to make time to be with my family, however busy I am. Abstract : Focusing on the recent progress in Chen's group, this review summarizes the main factors affecting the catalytic performance of nano‐catalysts, including structure, composition, size, and interface.